Cohesion in News Articles: A Discourse Analysis of Two News Articles From BBC And TOLO News About Overturning The Courts’ Decision For Ahmad Omar Sheikh - Nazifullah Nijat (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2022)
The purpose of the current study is to identify various types of cohesive devices and their usage in the selected news articles about the courts’ decision for British-born Ahmed Omar Saeed Sheikh who is convicted of killing US journalist Daniel Pearl; published in Tolo News and BBC News websites. The data is analysed based on the cohesion model proposed by Holiday and Hasan (1976). Cohesions are semantic connections or “relationships of meanings within the text that describe it as a text” (Halliday and Hasan, 1976). The findings of the study show that grammatical cohesive devices containing references, conjunctions, substitution and ellipsis as well as lexical cohesions involving repetitions and collocations were found in both news articles. Among other grammatical cohesive devices, references were found to be frequently used in both news articles while repetitions were the most frequently occurred cohesive devices among lexical cohesion. It can be concluded that all the mentioned cohesive devices employed in the text ultimately contributed to the meaning of the text by binding it in an organised way. It also has been observed that writers use cohesions to give a sense of connection and order to the text.